The Effect Of NPK Fertilizer Doses And Biofertilizers On The Growth Of Sugar Cane Chips Bud (Saccharum Officinarum L.) Seedlings - Febridayanti, Fika; Setiyono, Setiyono; Farisi, Oria Alit; Savitri, Dyah Ayu; Arum, Ayu Puspita; Meliala, Susan Barbara Patricia Sembiring; Nisak, Fauziatun (International Journal on Food, Agriculture and Natural Resources, 2025)
The need of sugar cane for sugar production continues to increase yearly as human population increasing. Based on Central Bureau of Statistics, sugar cane production in Indonesia grew by 3.54% per year. However, this growth is not sufficient to meet the sugar demand of 2.70 million tons. The cause of Indonesia's low sugar production can be seen from the on-farm side, namely seed preparation. Preparing seeds using conventional methods (mules) affects the seeding time because it takes 6 months for one planting period. The experimental design was carried out using the basic pattern of a Completely Randomized Factorial Design consisting of two factors with three replications. Factor I, namely the dose of NPK inorganic fertilizer (16:16:16) and Factor II, namely the dose of Sinarbio biological fertilizer. The results of the research were (1) The interaction between the treatment of NPK fertilizer doses and biofertilizer doses on the growth of sugarcane bud chip seedlings had a significant effect on shoot length and an insignificant effect on the variables number of leaves, stem diameter, number of tillers, root volume, root wet weight and root dry weight. (2) The effect of NPK fertilizer dosage on the growth of sugarcane bud chip seedlings had no significant effect on all observed variables except root wet weight and number of tillers. (3) The effect of biofertilizer dosage on the growth of sugarcane bud chip seedlings had no significant effect on all observed variables except root volume.